Fathomless - Pearce, Jackson (New York Little, Brown and Company, 2012)
Celia, who shares mental powers with her triplet sisters, finds competition for a handsome boy with Lo, a sea monster who must persuade a mortal to love her and steal his soul to earn back her humanity.
Keywords: Sea monsters -- Sea stories -- Sisters